Auditoría a los controles utilizados en los cobots, para evitar fraudes en procesos industriales (2020)
In the article, the characteristics of cobots are identified which allow the development of collaborative work with humans, causing industrial processes to be carried out with efficiency, high quality standards, opportunity and cost reduction. On the other hand, vulnerabilities that impact cobots with a high-risk severity, in software and hardware are determined through remote and physical attacks, which can manipulate this technology, causing from the theft of classified information to damage in the human resource for injuries. Therefore, the existing controls in the cobots are identified and evaluated, applying the ISO 19011 methodology supported by risk management (ISO 31000), obtaining as a result that the controls are not efficient, nor appropriate to mitigate risks, therefore, It is recommended that systems audits be implemented, such as a detective control, which should be carried out periodically in order to evaluate the state of the controls and in turn analyze whether it is necessary to implement new controls.